Drying of leek slices using heated air - Doymaz, Ibrahim (WILEY-BLACKWELL, 2008)
The drying characteristics of both blanched and unblanched leek slices were investigated for a temperature range of 60-80C and a constant air velocity of 2.5 m/s. They were investigated as a function of drying parameters, air temperature, slice thickness and pretreatment by hot water at 70C. The temperature of the drying air and slice thickness were observed to be significant factors affecting drying. The experimental data was fitted to four thin-layer drying models available in the literature. Goodness of fit by these models was based on comparing the coefficient of determination (R(2)), reduced chi-square (chi(2)) and root mean square error (RMSE) between the observed and predicted variable. The Midilli et al. model was the most adequate in describing thin-layer drying tests. Both drying air temperature and slice thickness had pronounced influences on the values of effective moisture diffusivity (D(eff)). The values of D(eff) varied from 2.487 to 5.556 x 10(-10) m(2)/s for blanched samples, and from 1.909 to 4.140 x 10(-10) m(2)/s over the temperature range investigated. The values of activation energy were found to be 35.73, 18.09 and 30.16, 17.54 kJ/mol for blanched and unblanched leek samples with 1- and 2-cm thickness, respectively.
Keywords: SWEET-POTATO SLICES; PUMPKIN SLICES; HOT AIR; KINETICS; QUALITY; MODEL; PRETREATMENTS; DEHYDRATION; TEMPERATURE; MICROWAVE; Engineering; Food Science & Technology